2020
DOI: 10.36303/sajaa.2020.26.3.2431
|View full text |Cite
|
Sign up to set email alerts
|

Africa’s critical care capacity before COVID-19

Abstract: Critical care capabilities in affluent countries have been overwhelmed by the 2019 novel coronavirus disease (COVID-19) pandemic. Data from the African Surgical Outcomes Study (ASOS)1 suggests that this critical care crisis will be significantly worse in Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 3 publications
2
29
0
Order By: Relevance
“…First, the scarcity of critical care resources in African countries might contribute to the high critical care mortality. Second, there are inadequate critical care beds, 4 with only one in two patients referred to critical care being admitted. Yet, the full SOFA scores suggest that the patients who were admitted could be relatively healthier than patients admitted in countries with more critical care resources (appendix p 31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the scarcity of critical care resources in African countries might contribute to the high critical care mortality. Second, there are inadequate critical care beds, 4 with only one in two patients referred to critical care being admitted. Yet, the full SOFA scores suggest that the patients who were admitted could be relatively healthier than patients admitted in countries with more critical care resources (appendix p 31).…”
Section: Discussionmentioning
confidence: 99%
“…Our hypothesis was that critically ill patients with COVID-19 might have worse health outcomes in Africa than other continents because the ability to provide sufficient care is compromised by having a small workforce, 3 having a low number of intensive care facilities, and the scarcity of critical care resources. 4 We also hypothesised that unplanned admissions would further adversely affect critical care outcomes in Africa 5 as the ability of health-care systems to respond to meet the clinical workload is limited. Finally, patient outcomes following critical care for COVID-19 were not sufficiently documented in this under-resourced environment, 6 despite a call for prevention and response measures in low-income and middle-income countries.…”
Section: Introductionmentioning
confidence: 99%
“…COVID‐19 has brought to the fore the limited capacity of most African countries to respond to health emergencies, which is highlighted by recent studies emphasising the deficiencies in health systems across the African continent. 2 , 3 , 4 A recent survey revealed that there is less than one intensive care bed per 100,000 people across Africa. 3 Another report concluded that healthcare systems across the continent are under‐resourced, with lower proportions of available hospital beds, intensive care units, and health professionals than other regions of the world.…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 3 , 4 A recent survey revealed that there is less than one intensive care bed per 100,000 people across Africa. 3 Another report concluded that healthcare systems across the continent are under‐resourced, with lower proportions of available hospital beds, intensive care units, and health professionals than other regions of the world. 4 For instance, in Nigeria, the national health authorities reported that they are struggling with bedspace for COVID‐19 patients as the number of cases increase and home care for COVID‐19 patients is being considered.…”
Section: Introductionmentioning
confidence: 99%
“…The disproportionate spread of Covid-19 across and within countries in SSA has not followed a homogenous pattern with the heterogeneity attributed to a country's ability to prevent, detect and mount response strategies [7][8][9]. This has been exacerbated by incomplete documentation on Covid-19 cases and deaths across the continuum of care [10] due to ine cient and unreliable disease surveillance systems, scarce critical care resources, grossly underfunded and inadequate healthcare facilities, insu cient training of healthcare workers [11][12][13]. Additionally, its interaction with poverty-related non-communicable diseases (NCDs) has led to adverse medical outcomes/attributable deaths that are yet to be fully quanti ed [14][15][16].…”
Section: Introductionmentioning
confidence: 99%